Physiologic modulation of natural killer cell activity as an index of Alzheimer's disease progression - Prolo, Paolo (Biomedical Informatics Publishing Group, 2007)
Patients with Alzheimer's disease (AD) are characterized by an altered sensitivity to cortisol-mediated modulation of circulating lymphocytes. Longitudinal studies are needed to address the clinical applicability of these abnormalities as prognostic factors. Therefore, we designed a longitudinal study to address the clinical applicability of physiologic modulation of Natural Killer (NK) cell activity as a prognostic factor in AD. NK activity was assessed as baseline measurement and in response to modulation by cortisol at 10(-6)M. To verify the immunophysiological integrity of the NK cell population, we tested augmentation of NK cytotoxicity by human recombinant interleukin (IL)-2 (100 IU/ml) as control. The response to modulation by cortisol or by IL-2 was significantly greater in patients with AD. Based on change in the Mini-Mental State score at entry and at 18 months, patients with AD could be assigned to a “fast progression” (Δ > 2 points) or to a “slow progression” group (Δ ≤ 2 points). The change in the response of NK cytotoxic activity to cortisol, and the strength of the association of this parameter with circulating activated T cells in time was greater in patients with Fast Progression vs. Slow Progression AD. These results suggest that changes in the response of NK cells to negative (e.g., cortisol) or positive modifiers (e.g., IL-2) follow progression of AD.